The Eastern Pacific species of Bathygobius (Perciformes: Gobiidae) - Miller, Peter J. (2001)
The circumtropical gobiid genus Bathygobius Bleeker is defined and three Eastern Pacific species are redescribed, with first dorsal fin pattern and postorbital blotches being shown to be additional characters of diagnostic value. Two mainland species are recognised, the Mexican-Panamanian B. ramosus Ginsburg 1947 and the Panamanian B. andrei (Sauvage 1880). B. ramosus is now reported from Clarión Island, Revillagigedos, and also from Cocos Island. Meristic variation of ramosus is tabulated for local populations and PCAanalysis of their morphometry suggests regional differentiation in this species, with Tres Marias and Revillagigedos populations clustering away from mainland and Montuosa material. An insular species, B. lineatus (Jenyns 1842) from the Galapagos is defined, with B. arundelii (Garman 1899) from Clipperton Island and B. l. lupinus Ginsburg 1947 from Lobos de Afuera, off Peru, placed as nominal subspecies of lineatus. This species resembles the Indo-west Pacific B. fuscus and Atlantic basin B. soporator more closely than it does ramosus and andrei and may be the product of transpacific dispersal. A similar origin for B. ramosus is discussed but it seems more likely that both B. ramosus and B. andrei have Caribbean sister species.